Rancang Bangun Sistem Penjualan dan Stok Opname Berbasis Web pada PT Berkah Jaya Awing - Taufiq Hidayatur Romadlon; Farizi Ilham; Vicky Irmansyah; Ferdi Zandio (CV. Shofanah Media Berkah, 2026)
PT Berkah Jaya Awing previously recorded sales and managed inventory manually using paper receipts and ledgers. This condition created several operational problems, including recording errors, delayed report preparation, and inconsistencies between physical inventory and administrative records. This study aims to design and develop a web-based sales and stock opname information system to support transaction processing, inventory control, and centralized reporting. The development method used in this study is the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using PHP, MySQL, Apache, and XAMPP. Its main features include user authentication, an admin dashboard, item data management, Point of Sale transactions, stock opname, low stock notifications, and sales reports. The implementation results indicate that the system supports digital transaction recording, more structured inventory updates, and faster sales report preparation. This system is expected to improve administrative efficiency and inventory data accuracy in the company